Les terres australes françaises, terrain d’expérimentation de la solidarité écologique - Paul Tixier; Christophe Guinet; Chloé Faure; Anatole Danto; Camille Mazé (VertigO)
Human-Wildlife coexistence, crystalizing trade-offs between socio-economic viability, food security of human populations and species conservation, has become a major societal and environmental challenge. This challenge represents an experimental framework for putting the principle of ecological solidarity to the test in the field. In the oceans, the global conflict between fisheries and megafauna has recently intensified but its mitigation is hampered by complex stakes in local socio-ecosystems and a lack of cross-sectorial expertise and management. Using the longline fishery operating off Crozet and Kerguelen (French subantarctic islands) as a case study, and to propose social-ecological systems models that can be implemented in other similar situations, we examined how players have mobilized and reorganized in response to two severe conflicts: seabird bycatch and depredation by cetaceans (species feeding on fishery catches).